PENGARUH PENGGUNAAN MODEL DISCOVERY LEARNING BERBANTUAN MIND MAPPING TERHADAP KETERAMPILAN MENULIS TEKS BIOGRAFI SISWA KELAS X SMA NEGERI 3 BUKITTINGGI - Mandasari, Citra; R.,, Syahrul (Universitas Negeri Padang, 2019)
ABSTRACTÂ The purpose of this study is to (1) describe the skills of writing biographical texts of class X SMA Negeri 3 Bukittinggi before using mind mapping assisted discovery learning models, (2) describe the biography text writing skills of class X Bukittinggi SMA 3 students after using mind-assisted discovery learning models mapping, and (3) analyzing the influence of the use of discovery learning models assisted by mind mapping on biography text writing skills of class X Bukittinggi 3 Public High School students. This type of research is quantitative research with experimental methods. The design of this study is One Group Pretest and Posttest Design. The population of students in class X of SMA Negeri 3 Bukittinggi was 352 students spread in ten classes. The sample in this study were students of class X MIPA 1 Bukittinggi State High School 3. The variable in this study is the writing biographical skills of students before and after using mind mapping assisted discovery learning models. The instruments used in this study were performance tests. The data of this study are scores on the results of biographical text writing skills tests for class X students of SMA Negeri 3 Bukittinggi before and after using mind mapping assisted discovery learning models. Kata Kunci: Pengaruh, Discovery Learning, Mind Mapping, Keterampilan Menulis Teks Biografi.